Visible Solidarities: #Asians4BlackLives and Affective Racial Counterpublics - Kuo, Rachel (Studies of Transition States and Societies, 2017)
This article examines how uses of ‘Asian-ness’ as racial presence becomes used discursively and visually to form affective racial counterpublics around #Asians4BlackLives/#Justice4AkaiGurley and #SavePeterLiang/#Justice4Liang. Specifically, I look at how how Asian American racial positioning becomes deployed in order to produce feelings of solidarity. Approaching hashtags as both indexical signifiers of solidarity and as an indexing system that archives together an array of media objects, I track media objects across multiple sites in order to examine visual modes of storytelling that affectively mobilize publics and investigate solidarity as discursively mediated, embodied, and affective phenomena. I closely examine how #SavePeterLiang protestors create narratives of victimization in response to the singularity of Liang’s racial body and how the #Asians4BlackLives selfie project uses representational visibility to activate affective politics.